The assessment of postoperative cholangitis in malignant biliary obstruction: a real-world study of nasobiliary drainage after endoscopic placement of self-expandable metal stent - Jin, Hengwei; Fu, Chang; Sun, Xu; Fan, Changqing; Chen, Junhong; Zhou, Hao; Liu, Kai (Frontiers in Oncology, 2024)
ObjectivesEndoscopic retrograde cholangiopancreatography(ERCP) with endoscopic metallic biliary endoprosthesis(EMBE) serves as a crucial palliative treatment for advanced malignant biliary obstruction(MBO). While endoscopic nasobiliary drainage(ENBD) effectively reduces post-ERCP cholangitis (PEC) incidence, its impact on PEC in MBO patients is unclear. This study evaluates ENBD’s effects on PEC in patients undergoing EMBE and identifies risk factors.MethodsThis retrospective cohort study at the First Hospital of Jilin University involved MBO patients who underwent EMBE from September 2011 to September 2022. Propensity score matching (PSM) was applied to minimize selection bias. Primary and secondary outcomes included the incidence and recovery rate/time of PEC, biliary drainage success, and hospitalization duration. Univariate, multivariate, and Lasso regression analyses identified independent risk factors.ResultsIn this study of 1,008 patients, 730 were analyzed after PSM(365 each in the EMBE+ENBD and EMBE groups). No significant differences were observed in PEC incidence(10.7% vs 11.2%, p=0.9057) or recovery rates(48.7% vs 31.7%, p=0.1855). However, PEC recovery time was shorter in the EMBE+ENBD group(4.0 days [3.0, 6.0] vs 5.0 days [4.0, 7.5], p=0.0240), as was hospitalization duration(6.0 days [4.0, 8.0] vs 7.0 days [5.0, 10.0], p=0.0146), and a higher success rate of biliary drainage(54.0% vs 43.3%, p=0.0049). Tumor location(HR 1.10, 95% CI 1.00-1.20) and preoperative total bilirubin(HR 2.13, 95% CI 1.66-2.73) were identified as independent risk factors.ConclusionIn this large-scale PSM study, ENBD did not reduce PEC incidence but expedited recovery and shortened hospital stays. Patients with hilar MBO of Bismuth III-IV or high preoperative bilirubin were more prone to PEC.